Protective coatings on medical implants by reactive diffusion; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Gutmanas E. Y. Elazar (2014, 2014)
Title screen